Reverse shoulder arthroplasty for fracture sequelae: How the initial fracture treatment influences the outcomes of joint replacement - Fernando Santana; Eduard Alentorn-Geli; Pau Guirro; Carlos Torrens (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to analyze and compare the results of reverse shoulder arthroplasty (RSA) in proximal humeral fracture sequelae (PHFS) in fractures initially treated conservatively versus those initially treated with open reduction and internal fixation (ORIF). Methods: It is a retrospective study that includes all PHFS treated with a RSA from September 2006 to December 2013. Twenty-seven patients met the inclusion criteria. There were 9 patients (7 females and 2 males; mean age: 79.11 years) treated with RSA due to a fracture sequelae following conservative treatment and 18 patients (15 females and 3 males; mean age: 76.83 years) treated with a RSA owing to a fracture sequelae after ORIF.The functional outcome was recorded with the aid of the pre-surgery Constant Score and at the latest follow-up (minimum of two years). All the patients included underwent an imaging study that included plain X-Rays and a CT scan prior to surgery and plain X-Rays after surgery. All complications and reoperations during follow-up were also recorded. Results: Both groups had significantly increased Constant Scores after surgery (p < 0.0001), but the patients in the conservative group had significantly better outcomes for the total Constant Score (p = 0.024), for forward elevation (p = 0.026) and for external rotation (p = 0.004).A total of 4 complications (14.8%) were present during the follow-up period. In the conservative group, 1 patient developed an infection and there were 2 dislocations and 1 infection in the ORIF group. Conclusion: The use of RSA in the treatment of PHFS results in a limited outcome improvement but with an acceptable complication rate. Patients developing PHFS after conservative treatment may expect better outcomes and fewer complications than those developing PHFS after ORIF. Level of evidence: Level IV, Therapeutic Study. Keywords: Reverse shoulder arthroplasty, Proximal humeral fracture, Fracture sequelae, Open reduction, Internal fixation